Influence of American and British English on Pakistani Learners’ Vocabulary: A Study of Attitudes and Choices - Anwar, Nazia; Malik, Moazzam Ali (Pakistan Languages and Humanities Review, 2025)
The present research addresses the influence of the American and the British English on the Pakistani learner’s vocabulary in the light of their attitude and preference along with the socio- cultural factors that influence their vocabulary. The research has aimed at determining what variety of English either American or British, Pakistani students prefer and how education and social media as well as socio-cultural backgrounds impact their decision. English is an official and educational language in Pakistan but students are getting increasingly exposed to different global versions of the language in the social media, technology and entertainment. The current study has applied a mixed methods design for a data of 100 students of the university, a semi-structured interview and questionnaires. Quantitative analysis has revealed that 58 percent of learners were rather oriented to American vocabulary primarily due to the contact with media and the presence of the online version and 37 percent to the prestige of academic and formal English, which was British. Another pragmatic adaptation has also been identified in the qualitative data which is pragmatic alternation among the varieties by the learners depending on the context and the communicative purpose. The findings illustrate that the Pakistani learners are bilinguals which is attributed to the hybrid nature of the Pakistani English. The study has concluded that globalization and the educational traditions are all implicated in the process of the vocabulary choices of the learners. The study recommends that English language teaching in Pakistan need to adopt and integrate the two varieties so as to facilitate lexical awareness and communicative fluency.